Behavioural Logic and its Role in Evolving Micro-foundations Concept in Strategic Management: A Literature Review - Katarzyna PIÓRKOWSKA (Communications of International Proceedings, 2024)
The paper fills the research gap concerning a theoretical background for the micro-foundations concept in strategic management. It aims to explore the role of behavioural logic in evolving the micro-foundations in strategic management. The method that has been used is a critical literature review of the following concepts: micro-foundations, the behavioural theory of the firm, behavioural economics, strategic management, multi-level approach, and methodological individualism. The overarching findings are as follows. The concepts within the behavioural theory of the firm as bounded rationality, attention, learning, mental limitations, seeking information, dynamic nature of aspiration, proceeding information, conflict of interests, social relationships, and cooperation are the background of categories at the individual level. The concepts as conflict of interests, team cooperation, attention in teams, conflict of interests, team cooperation, career path, and bounded rationality are the background of the categories at the team level. The concepts as bounded rationality, standardised practices and programmes, operational procedures, habits, learning, responses and dependence to environment, organisational heterogeneity, organisational structure, hierarchic power, and hierarchic decision-making are the background of the following at the organisational level. The concepts within behavioural economics as bounded rationality, heuristics, ecological rationality, aspiration levels, economic opportunism, and adaptive heuristics are the background of the categories at the individual level. The concepts as habits, cognitive individual limitations, ecological rationality, adaptive heuristics, and aspiration level are the background of the categories at the organisational level. Sixth, making decisions under uncertain and complex conditions is the antecedent of researching environmental categories like dynamics, complexity, and uncertainty.
Keywords: multi-level research; micro-foundations; behavioural theory of the firm; behavioural economics.